Metabolic Syndrome Induces Release of Smaller Extracellular Vesicles from Porcine Mesenchymal Stem Cells. Issue 9 (September 2019) - Conley, Sabena M.; Shook, John E.; Zhu, Xiang-Yang; Eirin, Alfonso; Jordan, Kyra L.; Woollard, John R.; Isik, Busra; Hickson, LaTonya J.; Puranik, Amrutesh S.; Lerman, Lilach O.
Mesenchymal stromal/stem cells (MSCs) belong to the endogenous cellular reparative system, and can be used exogenously in cell-based therapy. MSCs release extracellular vesicles (EVs), including exosomes and microvesicles, which mediate some of their therapeutic activity through intercellular communication. We have previously demonstrated that metabolic syndrome (MetS) modifies the cargo packed within swine EV, but whether it influences their phenotypical characteristics remains unclear. This study tested the hypothesis that MetS shifts the size distribution of MSC-derived EVs. Adipose tissue-derived MSC-EV subpopulations from Lean ( n = 6) and MetS ( n = 6) pigs were characterized for number and size using nanoparticle-tracking analysis, flow cytometry, and transmission electron microscopy. Expression of exosomal genes was determined using next-generation RNA-sequencing (RNA-seq). The number of EV released from Lean and MetS pig MSCs was similar, yet MetS-MSCs yielded a higher proportion of small-size EVs (202.4 ± 17.7 nm vs. 280.3 ± 15.1 nm), consistent with exosomes. RNA-seq showed that their EVs were enriched with exosomal markers. Lysosomal activity remained unaltered in MetS-MSCs. Therefore, MetS alters the size distribution of MSC-derived EVs in favor of exosome release. These observations may reflect MSC injury and membrane recycling in MetS or increased expulsion of waste products, and may have important implications for development of adequate cell-based treatments.